Pengaruh Proses Rolling terhadap Struktur Mikro dan Sifat Mekanis pada Kuningan setelah diproses ecap - Julyadi Julyadi; Suryadi Suryadi; Erwin Siahaan; Eddy S. Siradj (Program Studi Teknik Mesin Universitas Tarumanagara, 2014)
Abstract: Brass material widely used in industry because it has the advantage of being a metal that resists corrosion, has high ductility, good toughness and easy on the form. This study was conducted to determine the effect of rolling process on mechanical properties and microstructure of metal brass after ECAP process on brass (CuZn) 70/30. The initial step is to make the specimens with a diameter of 10 mm and height 80 mm has been done annealing 600 ° C with a hold time of 90 minutes. Then a ECAP 3-pass process and cold rolling process. To determine the mechanical properties of tensile test specimens and hardness test) and metallographic observations to determine the microstructure. The results after the execution of the research note that the specimen after passing through annealing process, ECAP and rolling have a higher hardness. Prior to treatment the specimen hardness value is 78 VHN and after treatment to 252 VHN hardness value. Metallographic observations of known properties of brass increasingly refined microstructure and grain boundary between micro become increasingly tight.